2023
DOI: 10.1146/annurev-pathol-042320-112212
|View full text |Cite
|
Sign up to set email alerts
|

Tuft Cells: Context- and Tissue-Specific Programming for a Conserved Cell Lineage

Abstract: Tuft cells are found in tissues with distinct stem cell compartments, tissue architecture, and luminal exposures but converge on a shared transcriptional program, including expression of taste transduction signaling pathways. Here, we summarize seminal and recent findings on tuft cells, focusing on major categories of function—instigation of type 2 cytokine responses, orchestration of antimicrobial responses, and emerging roles in tissue repair—and describe tuft cell–derived molecules used to affect these func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 145 publications
1
25
0
Order By: Relevance
“…In addition to the intestine, tuft cells have been identified in the lung, trachea, esophagus, stomach, thymus, pancreas, and biliary tract, and contribute to airway hypersensitivity. [42][43][44][45][46][47][48] Interestingly, HDAC3 is expressed ubiquitously, and butyrate levels at extra-intestinal sites reflect microbiota colonization. Thus, it is plausible that butyrate regulation of HDAC3 may control tuft cell-dependent immune responses at distant tissue sites as well.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the intestine, tuft cells have been identified in the lung, trachea, esophagus, stomach, thymus, pancreas, and biliary tract, and contribute to airway hypersensitivity. [42][43][44][45][46][47][48] Interestingly, HDAC3 is expressed ubiquitously, and butyrate levels at extra-intestinal sites reflect microbiota colonization. Thus, it is plausible that butyrate regulation of HDAC3 may control tuft cell-dependent immune responses at distant tissue sites as well.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 14, 2023. ; https://doi.org/10.1101/2023.04.14.536701 doi: bioRxiv preprint which would support their being Merkel cells. Alternatively, other scRNA-seq studies in mouse and human have shown that Hmx2 is expressed by tuft (brush) cells in gut and airway epithelia (Haber et al, 2017;Deprez et al, 2020), so it is possible the Hmx2-expressing skin cells in paddlefish are chemosensory epithelial cells, like tuft cells (Kotas et al, 2023).…”
Section: Mechanosensory-restricted Lateral Line Expression Of Hmx2 Is...mentioning
confidence: 99%
“…Tuft cells are solitary chemosensory cells found throughout epithelia of different organs (reviewed in [1]). Their numbers can increase dramatically upon infection, injury, or disease.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of taste receptors and the succinate receptor 1 (SUCNR1) on tuft cells enables them to detect environmental changes in metabolites [7,8]. They are also characterized by expression of signal transduction genes characteristic for taste buds [1]. Activation of taste/chemosensory receptors on tuft cells transduces environmental signals to other effector systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation